Increasing the level of security in the formation of common market - Ogannesovich Iskajyan, Simon; Kiseleva, Irina Anatolievna; Tramova, Aziza Muhamadiyaevna; Ivanovna Litovka, Natalya (Nexo Revista Científica, 2022)
This article discusses current issues of economic security of the EAEU countries and the need to create common market spaces with common rules and principles for all the countries of the union. In the context of continuous globalization, the development of international economic relations, and the integration of national economies, there are many common threats to economic security for all economic unions. The proposed methodology for assessing the level of economic security is based on a comprehensive analysis and assessment of the main strands of the economic policy of the Union countries and the possibilities of creating common markets in areas under consideration. Based on the analysis, the conditions for creating common rules and principles of economic policy of the EAEU countries are proposed to ensure the common economic security of the union.